2021
DOI: 10.1001/jama.2021.3331
|View full text |Cite|
|
Sign up to set email alerts
|

Four-Month Clinical Status of a Cohort of Patients After Hospitalization for COVID-19

Abstract: The Writing Committee for the COMEBAC Study Group IMPORTANCE Little is known about long-term sequelae of COVID-19.OBJECTIVE To describe the consequences at 4 months in patients hospitalized for COVID-19. DESIGN, SETTING, AND PARTICIPANTSIn a prospective uncontrolled cohort study, survivors of COVID-19 who had been hospitalized in a university hospital in France between March 1 and May 29, 2020, underwent a telephone assessment 4 months after discharge, between July 15 and September 18, 2020. Patients with rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

44
344
11
36

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 509 publications
(476 citation statements)
references
References 33 publications
44
344
11
36
Order By: Relevance
“…However, the exploration of patients with post-acute COVID-19 syndrome requires a multidisciplinary approach, as complications far exceed the problem of dyspnoea, and it appears that pulmonary and systemic complications can be intimately entangled. Among the many complications are general signs (asthenia, diffuse pain), psychiatric symptoms (post-traumatic stress syndrome, depression, anxiety, insomnia), neurological symptoms (cognitive impairment, dysautonomia), and specific organ lesions affecting cardiovascular, renal, endocrine, ear-nose-throat, gastrointestinal or dermatological systems (Table 1) [9][10][11][12][13][14][15][16]. Most patients with post-acute COVID-19 syndrome experience multiple and overlapping symptoms, in addition to a significant impact on their quality of life [10,[12][13][14][15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the exploration of patients with post-acute COVID-19 syndrome requires a multidisciplinary approach, as complications far exceed the problem of dyspnoea, and it appears that pulmonary and systemic complications can be intimately entangled. Among the many complications are general signs (asthenia, diffuse pain), psychiatric symptoms (post-traumatic stress syndrome, depression, anxiety, insomnia), neurological symptoms (cognitive impairment, dysautonomia), and specific organ lesions affecting cardiovascular, renal, endocrine, ear-nose-throat, gastrointestinal or dermatological systems (Table 1) [9][10][11][12][13][14][15][16]. Most patients with post-acute COVID-19 syndrome experience multiple and overlapping symptoms, in addition to a significant impact on their quality of life [10,[12][13][14][15].…”
mentioning
confidence: 99%
“…Among the many complications are general signs (asthenia, diffuse pain), psychiatric symptoms (post-traumatic stress syndrome, depression, anxiety, insomnia), neurological symptoms (cognitive impairment, dysautonomia), and specific organ lesions affecting cardiovascular, renal, endocrine, ear-nose-throat, gastrointestinal or dermatological systems (Table 1) [9][10][11][12][13][14][15][16]. Most patients with post-acute COVID-19 syndrome experience multiple and overlapping symptoms, in addition to a significant impact on their quality of life [10,[12][13][14][15]. Of note, such complications have been described in other post-acute settings and may not be specific to COVID-19 [17,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of documenting the long-term consequences of COVID-19, a well-conducted study was published by the COMEBAC (COnsultation Multi-Expertise de Bicêtre Après COVID-19) Study Group [17] . This landmark study was carried out in a third-level hospital in the Paris area and included more than 450 patients.…”
mentioning
confidence: 99%
“…Regarding intensive care unit (ICU)-treated patients, there is a need to evaluate the occurrence of post-intensive care syndrome (PICS) [7] because it has become recognized and is the next care target in the eld of critical care medicine [8-10].PICS is de ned as a new or worsening impairment in physical, mental, or cognitive health status that arises and persists after hospitalization for critical illness [7]. Although there have been recent reports regarding long-term consequences, including fatigue, insomnia, and anxiety or depression, among COVID-19 survivors at or 6 months after acute infection, information regarding critically ill patients remains missing [2,5, 6]. Small-scale studies investigating ICU treated patients with COVID-19 have suggested that respiratory, mobility, and cognitive consequences are common at approximately a month after hospital discharge [3, 6].…”
mentioning
confidence: 99%